STUDI PENETAPAN KADAR LOSARTAN DENGAN METODE SPEKTROFOTOMETRI DAN HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) SERTA APLIKASINYA PADA TRANSPOR TRANSDERMAL in vitro - Annas Binarjo; Achmad Kharis Nugroho (Universitas Ahmad Dahlan, 2013)
The development of drug delivery system needs a usefull determination method of drug in many kind of samples. This research was purposed to develop a determination method of losartan, an angiotension receptor antagonist II, from the sample of in vitro transdermal transport. Three methods were studied, i.e. normal spectrophotometric, 1st derivative spectrophotometric, and HPLC. The spectrophotometric method was conducted using Spectrophotometer Shimadzu tipe UV 1700 controlled by UV Probe software (Shimadzu), while HPLC method was performanced by Shimadzu HPLC controlled by LC Solution software (Shimadzu). Lichrospher RP 18 250-4 (5 µm) was used as stationary phase and acetonitril-acetic buffer 0,01 M pH 4 (60:40) was used as mobile phase. Chromatogram was recorded using UV 223 nm and 254 nm as a detector. Some parameters of determination method performance were calculated, i.e. LOD, LOQ, recovery, systemic error, and random error. The results shown that spectrofotometric methods did not have an enough performance parameters to use in transdermal transport of losartan, while HPLC method had LOD and LOQ 27,329 and 91,098 ng/ml using UV 223 nm as detector and 36,178 and 120,590 ng/ml using UV 254 nm as detector. Detector UV 223 nm was selected. This HPLC method had recovery 106,405% and random error 3,71%, and could be used to determine the losartan concentration in sample from transdermal transport in vitro.